2015
DOI: 10.1111/jac.12117
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation for Salinity Tolerance in Pakistani Rice (Oryza sativa L.) Germplasm

Abstract: Soil salinity is one of the major production constraints. Development and planting of salt‐tolerant varieties can reduce yield losses due to salinity. We screened 185 rice genotypes at germination stage in petri dishes under control, 50, 100 and 150 mm salt stress, and at seedling stage in Yoshida's hydroponic nutrient solution under control, 50 and 100 mm salt stress. At germination stage, 15 genotypes including Nona Bokra, Sonahri Kangni, 7421, 7423 and 7467, whereas at seedling stage, 28 genotypes including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 25 publications
4
30
0
Order By: Relevance
“…Tolerant Indica varieties are good Na + excluders, absorb high amounts of K + , and maintain a low Na + /K + ratio in the shoot [46]. This also demonstrates that there is a great variation in salinity tolerance among rice varieties [91][92][93][94].…”
Section: Conventional Breedingmentioning
confidence: 72%
“…Tolerant Indica varieties are good Na + excluders, absorb high amounts of K + , and maintain a low Na + /K + ratio in the shoot [46]. This also demonstrates that there is a great variation in salinity tolerance among rice varieties [91][92][93][94].…”
Section: Conventional Breedingmentioning
confidence: 72%
“…However, only a small proportion of these natural accessions have been assessed for traits under saline conditions using different screening approaches and experimental designs (Platten et al, 2013;Kumar et al, 2015). It has been found that the salt tolerance of cultivars of O. glaberrima and O. sativa is related to low Na + and high K + concentrations in roots and shoots (Reddy et al, 2014;Rahman et al, 2016;Sakina et al, 2016), and some of the most salttolerant cultivars are Pokkali, Nona Bokra, and FL478 (Zeng and Shannon, 2000;Platten et al, 2013). These salt-tolerant cultivars have been extensively used in breeding salinity-tolerant rice (Thomson et al, 2010;Platten et al, 2013;Reddy et al, 2014;Waziri et al, 2016).…”
Section: Search For Donors For Salt Tolerant Ricementioning
confidence: 99%
“…Salinity is one of the major issues responsible for reduction in agricultural yield (Flowers and Muscolo 2015). Salt affects the growth of crop plants by reducing the uptake of water by roots (Sakina et al 2016).The most critical phases of plant life are seed germination and growth of seedlings and these are adversely affected by various environmental changes especially salt stress (El-Soud et al 2013). Plants exposed to salinity stress undergo numerous physiological and biochemical changes because salt stress involves oxidative stress (El-Soud et al 2013).…”
Section: Discussionmentioning
confidence: 99%